Teacher's Strategy in Class Management in the Subject of Pancasila and Citizenship in Class VII A SMP Negeri 1 Kragilan - Indah Magfiroh, Sri; Ferani Nabilah, Estrella; Mukhlis, Mukhlis (LPPM Universitas Primagraha, 2022)
Classroom management strategies that can affect the learning process and the importance of the teacher's role in managing the class in order to improve student learning, especially Pancasila and citizenship education teachers, who in their lessons teach more about values, ethics, manners and discipline. The purpose of this study is to explain how the teacher's strategy in managing the Pancasila and civic education subjects in class VII A of SMP Negeri 1 Kragilan. This study uses a qualitative method with a descriptive approach. Data collection techniques using observation, interviews and documentation. Data analysis techniques were carried out with three stages of activity, namely data reduction, data presentation, and then drawing conclusions. The results of this study the strategy used by the teacher in class management in the subject of Pancasila Education and citizenship in class VII A of SMP Negeri 1 Kragilan must be able to pay attention to the characteristics of students, because not all students have the same characteristics or abilities and they also come from different backgrounds. different. Student characteristics are one of the learning design variables that are related to student backgrounds. That way, learning can be designed according to aspects that exist in students such as general abilities, expectations of learning, and their physical and emotional characteristics.